2020
DOI: 10.21203/rs.3.rs-18281/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

M2 Macrophagy-derived Exosomal MiRNA-5106 Induces Bone Mesenchymal Stem Cells towards Osteoblastic Fate by Targeting Salt-inducible Kinase 2 and 3

Abstract: Background Osteoblast differentiation is a vital process for fracture healing, and exosomes are nanosized membrane vesicles that can deliver therapeutic drugs easily and safely. Macrophages participate in the regulation of various biological processes in vivo , and macrophage-derived exosomes (MD-Exos) have recently been a topic of increasing research interest. However, few study has explored the link between MD-Exos and osteoblast differentiation. Herein, we sought to identify miRNAs differentially expressed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…11,12 Several lines of evidence implicated that macrophage participates in the progression of various diseases through secreting exosomes. 13 In earlier study, Tesch et al pointed out the number of macrophage in kidney is related to the serious of DN, damage of renal function and DN prognosis. They further revealed that the macrophage activation facilitates the degradation of the kidney function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Several lines of evidence implicated that macrophage participates in the progression of various diseases through secreting exosomes. 13 In earlier study, Tesch et al pointed out the number of macrophage in kidney is related to the serious of DN, damage of renal function and DN prognosis. They further revealed that the macrophage activation facilitates the degradation of the kidney function.…”
Section: Introductionmentioning
confidence: 99%
“…M1 macrophage promotes the development of DN through secreting pro‐inflammatory cytokines like IL‐1, IL‐6, and TNF‐α, while M2 macrophage inhibits the development of DN through secreting anti‐inflammatory cytokines as IL‐10 and Arg‐1 11,12 . Several lines of evidence implicated that macrophage participates in the progression of various diseases through secreting exosomes 13 . In earlier study, Tesch et al pointed out the number of macrophage in kidney is related to the serious of DN, damage of renal function and DN prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Mφ‐derived exosomes account for a large portion of circulating microvesicles in the blood (McDonald et al, 2014). M2Mφ‐derived exosomes have been reported to induce osteoblastic fate in bone mesenchymal stem cells (Xiong et al, 2020). However, in a recent study by Jiang et al (2018), bone marrow stem cell‐derived exosomes from OP patients inhibited osteogenesis by transporting miR‐21 into cells.…”
Section: Discussionmentioning
confidence: 99%
“…Research has highlighted the promising use of nanomedicine in osteogenic differentiation, with recent years seeing a surge in the development of nanomedicines for bone repair, in an effort to overcome the weaknesses of currently available strategies [13][14][15]. A number of nano-drug delivery systems have been designed to effectively locally deliver various drugs into fracture sites, with improved drug concentration and decreased side-effects [16][17][18].…”
Section: Introductionmentioning
confidence: 99%